2013
DOI: 10.1080/17441692.2013.845676
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the Millennium Development Goals: a literature review

Abstract: With the Millennium Development Goals (MDGs) showing uneven progress, this review identifies possible limitations arising from the MDG framework itself rather than extrinsic issues. A multidisciplinary literature review was conducted with a focus on limitations in the formulation of the MDGs, their structure, content and implementation. Of 1837 MDG-related articles, 90 met criteria for analysis. Articles describe MDGs as being created by only a few stakeholders without adequate involvement by developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(140 citation statements)
references
References 67 publications
0
121
0
8
Order By: Relevance
“…Though analyzing determinants of inequality is beyond the scope of this study, we speculate that measuring the progress of reaching MDGs by focusing on national means could lead to less policy attention paid to inequalities [36]. A 2010 UNICEF report found that progress measured by national aggregates often conceals large and widening disparities in child health—despite apparent statistical success in reducing under-five mortality, inequalities between the poorest and the richest households grew by more than 10% [37].…”
Section: Discussionmentioning
confidence: 99%
“…Though analyzing determinants of inequality is beyond the scope of this study, we speculate that measuring the progress of reaching MDGs by focusing on national means could lead to less policy attention paid to inequalities [36]. A 2010 UNICEF report found that progress measured by national aggregates often conceals large and widening disparities in child health—despite apparent statistical success in reducing under-five mortality, inequalities between the poorest and the richest households grew by more than 10% [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the years leading up to the formulation of the Sustainable Development Goals (SDGs) there was increasing awareness that the Millennium Development Goals (MDGs) insufficiently addressed equality and the reduction of inequalities [1], focused on and sought aggregated information (which some called the tyranny of national averages [2]), did not address within-country inequalities [3] and had a weak human rights approach [4]. This was noted in the United Nations General Assembly (UNGA) 2010 resolution that reviewed progress towards achieving the MDGs outcomes [5] and the UNGA 2015 resolution that established the goals of the SDGs-related targets [6].…”
Section: Introductionmentioning
confidence: 99%
“…But despite initially garnering much praise, the MGDs began to attract a flood of criticisms. Fehling et al [45] summarize these quite succinctly:…”
Section: Formalizing Artisanal and Small-scale Mining: Planning For Tmentioning
confidence: 99%
“…The first concerns the stability participation in ASM has provided, over the short-to medium-term, for these households. In recent years, a raft of studies [45,[47][48] have drawn attention to how scores of the region's subsistence farm households, struggling to survive in a liberalized agricultural market, have 'branched out' into ASM. For many, this move has helped to resurrect failing crops by putting them in a position to acquire crucial farm inputs such as fertilizers, which most African governments no longer subsidize.…”
Section: The Little Things…mentioning
confidence: 99%